1999
DOI: 10.1136/jech.53.5.277
|View full text |Cite
|
Sign up to set email alerts
|

Patterns of smoking in the Baltic Republics

Abstract: (J Epidemiol Community Health 1999;53:277-282)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
29
2

Year Published

2000
2000
2013
2013

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(38 citation statements)
references
References 5 publications
7
29
2
Order By: Relevance
“…Details of the survey methods have been described previously (Pudule et al, 1999). The surveys sought to include representative samples of the national population aged between 19 and 64 y (19 ± 65 in Lithuania) using the National Population Registers as the sampling frames.…”
Section: Methodsmentioning
confidence: 99%
“…Details of the survey methods have been described previously (Pudule et al, 1999). The surveys sought to include representative samples of the national population aged between 19 and 64 y (19 ± 65 in Lithuania) using the National Population Registers as the sampling frames.…”
Section: Methodsmentioning
confidence: 99%
“…37 Also, in Latvia and Lithuania, less educated people tend to smoke more compared with highly educated groups. 38 Thus, important targets of public health smoking cessation efforts are the less educated socioeconomic groups, particularly males. On the other hand, less educated women have been most frequently exposed to passive smoking in Estonia and Lithuania.…”
Section: Smoking Patterns In Candidate Statesmentioning
confidence: 99%
“…Estimates of cancer mortality for the year 2000 for all 10 accession countries were derived from the Globocan 2000 software and database. 13 Age-standardized mortality rates (ASRs) were calculated for all ages combined and for age groups [20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38][39][40][41][42][43][44][45][46][47][48][49][50][51][52][53][54][55][56][57][58][59][60][61][62][63][64][65][66][67][68][69][70][71][72][73][74] Hungary and Poland) and for age groups 20 -44, 45-64 and 65 and over (Estonia, Latvia, Lithuania, Slovakia and Slovenia) for each sex separately. The World Standard Population was used for age adjustment.…”
mentioning
confidence: 99%
“…12 Furthermore, the absolute number of elderly smokers are likely to increase as a consequence of global aging population. 8 Most studies, but not all, 1,24 have found that smoking is more frequent among men with lower socioeconomic condition and little formal education. 11 The objective of the present study was to describe the smoking habit of older adults living in the community and to examine the factors associated with current and past smoking.…”
Section: Introductionmentioning
confidence: 99%